Body mass index, adiposity and tumour infiltrating lymphocytes as prognostic biomarkers in patients treated with immunotherapy: A multi-parametric analysis. (March 2021) - Esposito, Angela; Marra, Antonio; Bagnardi, Vincenzo; Frassoni, Samuele; Morganti, Stefania; Viale, Giulia; Zagami, Paola; Varano, Gianluca M.; Buccimazza, Giorgio; Orsi, Franco; Venetis, Konstantinos; Mazzarella, Luca; et al.
Abstract: Background: We performed a multi-parametric analysis investigating the association between adiposity (as measured using body mass index [BMI] and computed tomography [CT]-based body composition), tumour infiltrating lymphocytes (TILs) and clinical outcomes in patients with advanced-stage cancer treated with immunotherapy in phase I clinical trials. Material and methods: All consecutive patients (N = 153) with metastatic solid tumours treated within immunotherapy-based phase I clinical trials between August 2014 and May 2019 at our institution were included. Baseline characteristics, BMI, TILs value and CT-assessed fat indices (total fat area [TFA], subcutaneous fat area [SFA] and visceral fat [VFA]) were collected. The primary endpoints were to evaluate the impact of these parameters on overall survival (OS) and progression-free survival (PFS). Kaplan–Meier method and Cox proportional-hazards model were used for survival analyses. Results: At both univariate and multivariate analyses, BMI was not associated with PFS neither when considered as continuous variable (HR 0.90, 95% CI 0.74–1.09, P = 0.28) nor as dichotomous variable (underweight/normal versus overweight/obese) (HR 0.79, 95% CI 0.55–1.14, P = 0.21). Interestingly, patients diagnosed with 'immunogenic' tumours and higher VFA/SFA ratio (1st and 2nd tertile versus 3rd tertile) presented an increased OS (HR 0.88, 95% CI 0.78–1.00, P = 0.047). Conclusion: Our analysis showed that patients with tumours that are already known as responsive to ICIs with higher VFA/SFA ratio presented an increased OS. Further studies are needed to elucidate the effect of adiposity on the host immune response to immunotherapy. Highlights: No association links adiposity and outcome in patients treated with immunotherapy. Patients responsive to immunotherapy with a higher VFA/SFA ratio have a better OS. The results of our analysis need to be confirmed in subsequent prospective studies.